The Silence of Gifted Women: An Analytical Study of Virginia Woolf's a Room of One's Own - Alguzo, Nouh Ibrahim Saleh (جامعة العلوم التطبيقية الخاصة - عمادة البحث العلمي والدراسات العليا, 2017)
تحلل هذه الدراسة الظلم التاريخي البطريركي للنساء من خلال مناقشة مقالة فيرجينيا وولف "غرفة تخص المرء وحده". من خلال المقال، وولف تطالب بحقوق متساوية للنساء لإعطائهم الفرصة للتعبير عن أفكارهم من خلال كتابة الأدب النسائي. تزعم وولف أن مخاوف النساء خلال عهدها والحقيقة أن كتاباتهن لم تؤخذ بجدية منعتهم من الكتابة. وبناء عليه، فإنها تقترح أن الخصوصية بالإضافة إلى الاستقلال المالي والاجتماعي متطلبات أساسية للتأليف. إن القصة التي ترويها وولف عن جوديث والتي لم تتلقي الدعم من عائلتها تظهر المعاملة المختلفة للأطفال بناء على جنسهم. هذه القصة تتضمن أن على المجتمع أن يقدر فكر النساء اللواتي ليس أقل ذكاء من الرجال.
This study examines the historical patriarchal oppression of women in light of Woolf’s views presented in A Room of One’s Own. In her essay, Woolf demands equal rights for women to give them the opportunity to express their thoughts through writing feminist literature. Woolf claims that the anxiety of women during her time and the fact that their writings were not taken seriously prevented them from writing. Accordingly, she suggests that privacy as well as financial and social independence are basic requirements of authorship. The story that Woolf recounts about Judith, who did not receive support from her family, shows the different treatment of children according to their gender. This implies that society should recognize the astuteness of women who are not less intellectual than their male counterparts.
Keywords: حقوق المراة -- الظلم الإجتماعي -- البطريركية -- المعتقدات الدينية -- النظام المالي -- القوائم المالية